Coordination of hypoxia adaptation and iron homeostasis in human pathogenic fungi - Chung, Dawoon; Haas, Hubertus; Cramer, Robert A. (Frontiers in Microbiology, 2012)
In mammals, hypoxia causes facilitated erythropoiesis that requires increased iron availability with established links between oxygen and iron in regulation of the transcription factor hypoxia-inducible factor. Therefore, cellular responses to hypoxia and iron starvation are linked in mammals and are host conditions that pathogens encounter during infection. In human pathogenic fungi, molecular mechanisms underlying hypoxia adaptation and iron homeostasis have been investigated. However, the interconnected regulation of hypoxia adaptation and iron homeostasis remains to be fully elucidated. This review discusses the potential transcriptional regulatory links between hypoxia adaptation and iron homeostasis in human pathogenic fungi. Transcriptome analyses demonstrate that core regulators of hypoxia adaptation and iron homeostasis are involved in regulation of several common genes responsible for iron acquisition and ergosterol biosynthesis. Importantly, iron starvation increases susceptibility of fungal cells to antifungal drugs and decreased levels of ergosterol, while key hypoxia regulators are also involved in responses to antifungal drugs and mediating ergosterol levels. We suggest that pathogenic fungi have developed a coordinated regulatory system in response to hypoxia and iron starvation through (i) regulation of expression of hypoxia-responsive and iron-responsive genes via cross-linked key regulators, and/or (ii) regulation of factors involved in ergosterol biosynthesis. Thus, both oxygen and iron availability are intimately tied with fungal virulence and responses to existing therapeutics and further elucidation of their interrelationship should have significant clinical implications.